Dissenting Opinion dan Concurring Opinion dalam Putusan Mahkamah Konstitusi - Haidar Adam (Prodi Hukum Pidana Islam Fakultas Syari’ah dan Hukum Universitas Islam Negeri Sunan Ampel Surabaya, 2017)
Abstract: This article discusses about dissenting opinion and concurring opinion in the decision of the Constitutional Court. Law enforcement can be done through the Constitutional Court in the form of law judicial review. The issue of dissenting opinion is regulated through Law No. 24 Year 2003 and Constitutional Court Regulation No. 6 of PMK Year 2005 concerning Procedural Law of Tests of Act. The phrase used in the Constitutional Court Law is “the different opinion of the judiciary members